PENINGKATAN HASIL BELAJAR PADA TEMA KEBERAGAMAN BUDAYA INDONESIA MENGGUNAKAN MODEL GAME BASED LEARNING (GBL) BERBANTU MEDIA SMART ADVENTURE BOX DIGITAL PADA SISWA KELAS 5 SDN TEGALKALONG - Zaskia Aulia; Anggita Dwi Maharani; Annisa Zahira; Hamidah Hamsyah; Rana Gustian Nugraha (STKIP Subang, 2026)
This study aims to improve student learning outcomes on the theme of Indonesian cultural diversity using the Game Based Learning (GBL) model assisted by Smart Adventure Box Digital media for fifth-grade students at SDN Tegalkalong. The background of this research is the low student learning outcomes caused by conventional lecture-based teaching methods that make students feel bored and have difficulty remembering factual data such as names of traditional houses, traditional clothing, typical foods, and traditional weapons. The research method used is Classroom Action Research (CAR) carried out in two cycles. Each cycle consists of four stages: planning, implementation, observation, and reflection based on the Kemmis and McTaggart model. The research subjects were 23 fifth-grade students. Data collection techniques used observation, tests, and documentation. The results showed that the application of the Game Based Learning model assisted by Smart Adventure Box Digital media significantly improved student learning outcomes. In the pre-cycle, the average student score was 56.96 with a completion rate of only 21.7%. In cycle I, the average score increased to 83.91 with a completion rate of 73.9%. In cycle II, the average score reached 83.04 with a completion rate of 78.2%. Improvement also occurred in student activeness, enthusiasm, and cooperation during learning. Thus, the Game Based Learning model assisted by Smart Adventure Box Digital media is effective in improving student learning outcomes on the theme of Indonesian cultural diversity in fifth grade at SDN Tegalkalong and can be used as an alternative innovative learning model in elementary schools.